Emotion Management in Hadith Perspective: A Study of Hadith Takhrij and Syarah - Risdianto, Mu’aafi Fitri (Journal of Takhrij Al-Hadith, 2024)
This study aims to discuss the hadith about emotional management. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about emotional management in Muslim's narration No. 4724. The results and discussion of this study indicate that the status of the hadith is of sahih quality that meets the qualifications of maqbul for the practice of Islam. This study concludes that the Hadith narrated by Muslim No. 4724 is relevant to be used as a reference in controlling emotions.